Development of Healthcare in Verkhotomsk Volost and Shcheglovsk in Late 19th - First Quarter of 20th Centuries - I. Y. Uskov (Tsentr nauchnykh i obrazovatelnykh proektov, 2017)
The article is devoted to problem of organization of practice of medical care in Kemerovo (Ust-Iskitimskoye village of Verkhotomsk volost of the Kuznetsk district of Tomsk province until 1918, Shcheglovsk city in 1918-1932) in the late 19th - first quarter of 20th centuries. The research urgency is caused by studying the practice of formation of organizational structure of health care at low territorial levels. The novelty of the research is seen in the statement of the problem and its historiographical solution on the example of Kemerovo. The author considers peculiarities of the organization of the work of the rural medical station in the volost village Ust-Iskitimskoye, practice of rural medicine and uphold of the principles of the Soviet system of health care in Shcheglovsk. The specified period is proposed to suggest the initial stage in the organization of urban health. The essential characteristics of this stage are determined. Special attention is paid to the establishing medical personnel. Biographical background is given. The collected empirical material allows to eliminate inaccuracies and errors in coverage problems available in the regional literature. The author believes that the presented results are applicable for further study of the history of health service of Kuzbass, and in the didactic purposes for the formation of a civic position of a future medical worker.